1994
DOI: 10.1016/s1063-4584(05)80064-0
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral distribution of the proximal tibia in gonarthrosis assessed in vivo by photon absorption

Abstract: Regional bone mineral density (BMD, g/cm2) of the proximal tibia including the subchondral plate was measured in vivo by dual photon absorptiometry (DPA). Twenty-one women and six men with gonarthrosis (GA) were examined. Twenty-four healthy women served as controls for the women. The precision error of the BMD measurements ranged from 1.4-3.7% depending on the region measured. Subchondral BMD correlated significantly to the radiologic stage (P < 0.05). Compared to the controls, BMD of the subchondral plate, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…Studies have shown that as disease severity in the knee increases there are localized increases in bone mineral density (BMD) and content of the proximal tibia (trabecular and/or cortical bone). These finding suggest that progressive hardening of the bone may be a part of the natural history of knee OA and not just an end-stage result [3][4][5][6][7]. A high BMD does not always indicate a pathological state.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies have shown that as disease severity in the knee increases there are localized increases in bone mineral density (BMD) and content of the proximal tibia (trabecular and/or cortical bone). These finding suggest that progressive hardening of the bone may be a part of the natural history of knee OA and not just an end-stage result [3][4][5][6][7]. A high BMD does not always indicate a pathological state.…”
Section: Introductionmentioning
confidence: 94%
“…Joint loads result from several factors including bony alignment and gait biomechanics. Varus/valgus knee angle and the frontal plane moments that result during gait have been related to bone mineral distribution in the proximal tibia in healthy and diseased knees, implicating them in the pathogenesis of OA [5][6][7]9]. Internal tibial torsion (tibias with lower than normal external torsion angles) and low femoral antetorsion angles have been linked with the incidence and severity of knee OA [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Data on bone mineral density (BMD) of the proximal tibia in osteoarthritic knees assessed in vivo by photon absorption were recently reported by Madsen et al (1994). Compared to the controls, BMD of the subchondral plate, BMD of the medial condyle, the medial to lateral distribution ratio of subchondral BMD, and the ratio between BMD of the subchondral plate and of the immediately underlying region were significantly increased in patients with predominantly medial osteoarthritis of the knee.…”
Section: Osteoarthritis Of the Kneementioning
confidence: 99%
“…Авторы выдвинули гипотезу, основанную на доказа-тельстве связи локальной МПК с распределением нагрузки внутри коленного сустава. Распределение этой нагрузки от-ражает отношение значений МПК в медиальных отделах большеберцовой кости к МПК в латеральных отделах -ме-диально-латеральный индекс (М/Л-индекс), который име-ет большее значение при варусной деформации [102][103][104]. При обследовании 268 человек (498 коленных суставов), из которых только 23% имели рентгенологически подтвер-жденный гонартроз, было выявлено, что в коленных суста-вах с локализацией отека костного мозга в медиальных уча-стках большеберцовой кости отмечался достоверно более высокий М/Л-индекс (р<0,0001) по сравнению с суставами без поражения костного мозга (и наоборот, более низкий -для латеральной локализации очагов отека).…”
Section: о б з о р ы научно-практическая ревматология 2011 № 1 50-57unclassified